Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijerph20032150
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Elderly Patients Hospitalized with the SARS-CoV-2 Omicron B.1.1.529 Variant: A Systematic Review

Abstract: The Omicron (B.1.1.529) variant of the severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) had an increased rate of spreading among the general population. Although this virus mutation resulted in milder symptoms, those on the vulnerable side of the population are still in danger of developing severe symptoms. Thus, this systematic review focused on identifying the clinical outcomes of older age patients (>65) that are hospitalized with the SARS-CoV-2 Omicron variant. The research was conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The emergence of new virus variants that differ in their genotype and phenotype from the first SARS-CoV-2 detected in this study, particularly the Omicron and its subvariants, can cause changes in their pathogenicity and transmissibility [ 64 ], which may in turn led to different clinical outcomes in COVID-19 patients. As the Omicron strains appear to be more transmissible and less pathogenic that the majority of the Omicron-infected cases tended to exhibit less severe or milder clinical manifestation than those infected with other variants, therefore a high-severity group would be narrowed down to the patient's characteristics of old age and having comorbidities [ 65 , 66 ]. Additionally, the introduction of COVID-19 vaccines to the Philippines during the time period of data collected [ 67 ] could have an impact on the immune characteristics of patients across different age groups [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of new virus variants that differ in their genotype and phenotype from the first SARS-CoV-2 detected in this study, particularly the Omicron and its subvariants, can cause changes in their pathogenicity and transmissibility [ 64 ], which may in turn led to different clinical outcomes in COVID-19 patients. As the Omicron strains appear to be more transmissible and less pathogenic that the majority of the Omicron-infected cases tended to exhibit less severe or milder clinical manifestation than those infected with other variants, therefore a high-severity group would be narrowed down to the patient's characteristics of old age and having comorbidities [ 65 , 66 ]. Additionally, the introduction of COVID-19 vaccines to the Philippines during the time period of data collected [ 67 ] could have an impact on the immune characteristics of patients across different age groups [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Omicron variant is more transmissible, data and many studies have shown that unlike the previous variants, the Omicron variant is less virulent and causes less severe illness and mortality [10][11][12][13][14]. However, it was worthy to note that Omicron cases in paediatric and elderly patients had a higher admission frequency [15][16][17][18]. Moreover, elderly populations with comorbidities such as diabetes, hypertension, cardiovascular disease, and chronic lung disease were more likely to develop severe symptoms [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was worthy to note that Omicron cases in paediatric and elderly patients had a higher admission frequency [15][16][17][18]. Moreover, elderly populations with comorbidities such as diabetes, hypertension, cardiovascular disease, and chronic lung disease were more likely to develop severe symptoms [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The identi ed genes include JAK1, PDE4A, SLC2A5, AK5, TMPRSS2 and RAB2A that all constitute as potentially therapeutic targets in multiple physiological systems. However, the patients in these studies were mostly recruited during 2020-2022 and therefore, infected with a mixture of several SARS-CoV-2 variants, resulting in heterogenous immune responses and symptoms 10 . Moreover, the majority of these studies are based on European ancestry, yielding results with uncertain translation to non-European populations.…”
Section: Introductionmentioning
confidence: 99%